2011
DOI: 10.3109/15368378.2011.622827
|View full text |Cite
|
Sign up to set email alerts
|

Exposure Limits: The underestimation of absorbed cell phone radiation, especially in children

Abstract: The existing cell phone certification process uses a plastic model of the head called the Specific Anthropomorphic Mannequin (SAM), representing the top 10% of U.S. military recruits in 1989 and greatly underestimating the Specific Absorption Rate (SAR) for typical mobile phone users, especially children. A superior computer simulation certification process has been approved by the Federal Communications Commission (FCC) but is not employed to certify cell phones. In the United States, the FCC determines maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
77
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(84 citation statements)
references
References 35 publications
1
77
0
3
Order By: Relevance
“…Even when not calling, cell phones emit a regular pulse of EMR when they are switched on [20]. An extensive number of experimental studies have indicated that pulsed digital radiation from cellular phones induced an array of biological impacts, including bloodbrain barrier disruption, liver damage, and eye damage [21][22][23]. Specifically, a relationship has been proposed between intensive cell phone use and an increased risk of brain cancer [23].…”
Section: Introductionmentioning
confidence: 98%
“…Even when not calling, cell phones emit a regular pulse of EMR when they are switched on [20]. An extensive number of experimental studies have indicated that pulsed digital radiation from cellular phones induced an array of biological impacts, including bloodbrain barrier disruption, liver damage, and eye damage [21][22][23]. Specifically, a relationship has been proposed between intensive cell phone use and an increased risk of brain cancer [23].…”
Section: Introductionmentioning
confidence: 98%
“…And it is reported that heating of tissue that exceeds 1 degree centigrade may interfere with behavioral and biological functions [27]. Gandhi et al [28] found that children's heads absorb over two times of RF than adults, and absorption of the skull's bone marrow can be ten times greater than adults. Tissues of the fetus, such as the central nervous system, seem especially vulnerable to temperature rises caused by high EMR in various time windows, particularly during organogenesis [29].…”
Section: Motivationmentioning
confidence: 99%
“…According to several authors, the finite-difference time-domain (FDTD) algorithm is the most widely accepted computation method for SAR modelling, because this method simulates more anatomic tissue models derived from MRI or CT scans (Chan et al 1997;Gandhi 2002;Gandhi et al 2011). In the FDTD method, every cell is modelled according to specifically defined tissue characteristics.…”
Section: Testing For Short Term and Long Term Exposuresmentioning
confidence: 99%
“…This is a large plastic head mannequin (Beard and Kainz 2004), with an opening at the top of its head, containing a liquid whose electrical permittivity and conductivity parameters are equivalent to the average electrical parameters of the 40 tissue types in the human head (Gandhi et al 2011). The size of the model head was initially based on the 90th percentile of 1989 United States military recruits (Gordon et al 1989).…”
Section: Testing For Short Term and Long Term Exposuresmentioning
confidence: 99%